Ligature of varicose veins by videoendoscopy in patients with upper digestive bleeding - María Elena Pérez Artímez; Jesús Fernández Duharte; Vladimir Brice Abreu; Sixto Alain Dinza Cabrejas; Gema de las Mercedes Colas Prevost (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: The esophageal varicose veins are vascular channels that unite the portal venous and systemic circulation. They are formed as consequence of the portal hypertension, predominantly in the submucosa of the inferior section of the esophagus. Objective: To characterize patients with break of esophageal varicose veins according to main clinical epidemiological and therapeutic-endoscopic variables. Methods: An observational, descriptive and longitudinal study of 20 patients with upper digestive bleeding due to break of esophageal varicose veins was carried out, they received endoscopic treatment with banding in the Gastroenterology Service of Dr. Juan Bruno Zayas Alfonso Teaching General Hospital in Santiago de Cuba, from November, 2016 to February,2018. In the statistical analysis the percentage was used as summary measure and the chi-square test was applied to identify the existence of some significant association among variables. Results: There was a prevalence of the male sex (80.0 %) and the 51 to 60 age group (40.0 %). Most of the patients presented liver cirrhosis (60.0 %) as cause of the portal hypertension and hematemesis (50.0 %) as form of upper digestive bleeding; also, the great size of the esophageal varicose veins was the main risk factor associated with the break (70.0 %) and, after the implementation of the endoscopic treatment, there was no second bleeding in almost all the patients (95.0 %). Conclusions: The application of this therapeutic procedure was satisfactory and it didn't cause any complication.